Motivational factors of senior athletes to participate in the Ironman - de Franco Tobar, L.; Teresinha Meurer, S.; Bertoldo Benedetti, T. R. (Science & Sports, 2013)
Introduction: To investigate the motivational factors of older adults who participate in sports events such as the Ironman. Summary of the results: In 2009, were interviewed 18 senior athletes registered in the Brazilian Ironman. The subjects were mainly motivated by pleasure and fun, challenge and competition, and improvement of health. In addition, most of the senior athletes received sponsorship and had triathlete friends. Conclusions: The present study allowed us to identify and better understand the motivational factors of senior athletes participating in the Ironman. These factors may contribute to increase or maintain the number of the participants in this group in future triathlon competitions.